(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2024)
Normalization is a step taken to correct variations in count rates between detection channels of small animals PET scanners. In general, in laboratory practice, normalization is performed using a commercial source of germanium 68. Given the half-life of the Ge-68 isotope, the normalization source must be replaced every two years at most, which generates a significant spent for the Laboratory. The objective of this work was to develop and test an alternative rechargeable source to be used on normalization routine. The results indicated that the rechargeable source (18F-FDG) can be used to replace the commercial source.